Effect of the oxygen content of pure copper powder on selective electron beam melting - Guschlbauer, Ralf; Burkhardt, Alex K.; Fu, Zongwen; Körner, Carolin (Materials Science and Engineering A-Structural Materials Properties Microstructure and Processing, 2020)
Additive Manufacturing using Selective Electron Beam Melting is attractive to fabricate pure copper components due to the specific properties of the electron beam. In this contribution, two different copper powder batches with different oxygen levels are processed. The samples produced using the powder with high oxygen level show cracks, whereas samples from the powder with low oxygen content are crack-free. The mechanical properties of the crack-free samples are investigated and compared to wrought and annealed copper.
CRIS-Team Scopus Importer:2020-03-06
Keywords: Additive manufacturing; Fractography; Mechanical properties; Pure copper; Selective electron beam melting

Grundlagen des selektiven Elektronenstrahlschmelzens von Reinkupfer - Guschlbauer, Ralf (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2022)

Process development for the manufacturing of 99.94% pure copper via selective electron beam melting - Lodes, Matthias; Guschlbauer, Ralf; Körner, Carolin (Materials Letters, 2015)
The additive processing of 99.94% pure copper powder via selective electron beam melting (SEBM) is presented. The high thermal and electrical conductivity of pure copper combined with the freedom in design in additive manufacturing is promising for future application e.g. as heat exchanger. A process window for the generation of dense copper parts could be evaluated. Despite the high thermal conductivity, comparatively low build temperatures have to be used due to the high sintering tendency of the powder. The latter also limits the maximum power input during melting.
Keywords: Additive manufacturing (AM); Process development; Pure copper powder; Selective electron beam melting (SEBM)

Process development of 99.95% pure copper processed via selective electron beam melting and its mechanical and physical properties - Guschlbauer, Ralf; Momeni, Soroush; Osmanlic, Fuad; Körner, Carolin (Materials Characterization, 2018)
Additive manufacturing by selective electron beam melting (SEBM) was used to fabricate pure copper specimens. A process window at process temperature of 530 °C, gives the required beam powers and deflection speeds for manufacturing dense specimens (>99.5%). The microstructure of SEBM specimens was analyzed by using optical and scanning electron microscopy (SEM). Electrical conductivity, thermal conductivity, hardness, and mechanical performance were investigated by using eddy current, laser flash analysis, Vickers hardness and tensile tests, respectively. It was found that the variation of beam power and scan speed results in different microstructures from columnar to nearly equiaxed grain. The electrical conductivity of SEBM-processed specimens was above 58 MS/m (>100 IACS) while their hardness was around 55 HV0.05 and 46 HV5 without any dependency on processing parameters within the process window. The tensile tests revealed how vertical cracks affect the mechanical strength under tensile loading condition. The results of this study not only show a reliable process window but also introduce the links between processing parameters, defect formations, conductivity and mechanical strength of pure copper specimens manufactured by SEBM.
Keywords: Process development; Pure copper powder; Mechanical properties; Microstructure; Selective electron beam melting; Conductivity

Selective electron beam melting of a copper-chrome powder mixture - Momeni, Soroush; Guschlbauer, Ralf; Osmanlic, Fuad; Körner, Carolin (Materials Letters, 2018)
Additive manufacturing by selective electron beam melting (SEBM) was used to process a powder mixture consisting of elemental copper and chromium powders (nominal composition: Cu-25Cr). The melting temperatures of copper and chromium are largely different. As a result, the copper particles start melting while the chromium ones are still solid. Eventually, also the chromium particles get molten since the local temperatures during SEBM are rather high. The microstructure was analyzed by scanning electron microscopy (SEM) and focused ion beam (FIB)-SEM. It was observed that ultra-fine Cr particles are formed and distributed in the Cu matrix due to the fast cooling rate and subsequent spinodal decomposition.
Keywords: Solidification; Spinodal decomposition; Electron beam melting; Microstructure; CuCr alloy; Additive manufacturing

Thermal and Electrical Conductivity of 99.9% Pure Copper Processed via Selective Electron Beam Melting - Raab, Sebastian; Guschlbauer, Ralf; Lodes, Matthias; Körner, Carolin (Advanced Engineering Materials, 2016)
This paper investigates the physical properties of 99.91% pure copper produced by Additive Manufacturing via selective electron beam melting (SEBM). Eddy current measurements and laser flash analyses are used to determine the electrical and the thermal conductivity. Electrical and thermal conductivity follow the Wiedemann-Franz law. The correlation of conductivities and porosity shows that 99.95 % dense components with nearly optimal conductivities (σ = 55.82 MS m and λ = 400.1 W m K) can be fabricated with SEBM. The small deviation from the theoretical maximum of copper (59.7 MS m) can be explained by the characteristics of the raw material and chemical impurities.